Delayed esophageal perforation occurring with endoscopic submucosal dissection: A report of two cases - Matsuda, Yasuhiro (World J Gastrointest Surg, 2015)
We report two cases of delayed esophageal perforation occurring with endoscopic submucosal dissection. Our cases involved delayed perforation after 10 d in case 1 and after 6 d in case 2. Both cases were related to solid food. We performed subtotal esophagectomy with gastric tube reconstruction of the esophagus via the subcutaneous route anterior to the thoracic wall without conservative treatment because both cases involved chest pain and major leakage of food into the mediastinum. Postoperative complications were a local factor (including suture failure and esophageal stricture) in case 1, and we performed endoscopic balloon dilatation five times for esophageal stricture. There was no intrathoracic and mediastinal infection in either case. Surgical treatment for delayed esophageal perforation can be performed safely and surely if diagnosis and assessment are not delayed.